2019
DOI: 10.26582/k.51.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity, approach-avoidance temperament and depressive symptoms

Abstract: The goal was to assess the connections between vigorous physical activity (VPA), approach-avoidance temperament and depressive symptoms. Two studies were conducted. Study 1, correlational, to assess the mediating role of both dimensions of temperament, approach-avoidance contrast, between physical activity and depressive symptoms. Participants, 335 college students, completed the International Physical Activity Questionnaire, the Depressive Symptoms Scale (DSS) and the Approach-Avoidance Temperament Questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
1
3
0
Order By: Relevance
“…Thus, participants had to answer six questions related to social activities that may affect their health "over the past 4 weeks" using a scale ranging from 1 to 4 ("often", "sometimes", "rarely" or "never"). Previous studies have reported acceptable reliability of this scale [21] as well as that obtained in the present study (Cronbach's alpha = 0.84 for the entire scale). Responses to the scale items were added up in order to obtain an overall depressive-symptom score ranging from 6 to 24 points.…”
Section: Methodssupporting
confidence: 86%
See 1 more Smart Citation
“…Thus, participants had to answer six questions related to social activities that may affect their health "over the past 4 weeks" using a scale ranging from 1 to 4 ("often", "sometimes", "rarely" or "never"). Previous studies have reported acceptable reliability of this scale [21] as well as that obtained in the present study (Cronbach's alpha = 0.84 for the entire scale). Responses to the scale items were added up in order to obtain an overall depressive-symptom score ranging from 6 to 24 points.…”
Section: Methodssupporting
confidence: 86%
“…Likewise, participants' depressive symptoms were recorded every 4 weeks (S1: 15 March; S4: 12 April; S8: 10 May) using the Spanish version [21] of Kandel and Davies' six-item self-report scale [22] adjusted to the confinement situation. Thus, participants had to answer six questions related to social activities that may affect their health "over the past 4 weeks" using a scale ranging from 1 to 4 ("often", "sometimes", "rarely" or "never").…”
Section: Methodsmentioning
confidence: 99%
“…Another, relatively larger, body of research has investigated differential associations of physical activity with depressive symptoms [ 15 , 16 , 37 ]. However, the understanding of the underlying factors determining these differential effects remains insufficient [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, individuals’ degree of self-determined motivation has been associated to depressive symptoms. Previous studies have shown the positive impact of autonomy support and self-regulation (self-determined motivation) on a variety of mental and physical health problems, including depression (Patrick and Williams, 2012) and depressive symptoms (Cecchini et al, 2017, 2019; Cecchini-Estrada et al, 2015). Similarly, participants’ perceived autonomy support and autonomous motivation while enrolled in a treatment programme were powerful predictors of treatment outcome (Kaap-Deeder et al, 2014).…”
Section: Discussionmentioning
confidence: 99%